PROFIL MISKONSEPSI SISWA PADA MATERI SUHU DAN KALOR - Yuliana, Ina; Artawan, Putu; Heny, Ajeng Purnama (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Misconception is a mismatch between the concept that a person believes and the scientific concept according to experts. The occurrence of misconceptions can affect one's knowledge of the next concept. This study aims to describe the profile of students ' misconceptions and find out the difficulties experienced by students on the material heat and temperature. This survey research was conducted on class X MA students totaling 24 students. Data were obtained through a web-based four tier diagnostic test consisting of 10 questions. Students' answers were categorized into 3 categories, namely understanding the concept, misconceptions, and not understanding the concept. The results showed that students had misconceptions with an average percentage of 41%. Students have the most misconceptions in the sub-material of the effect of heat on temperature changes with a percentage of 66%. Based on the results of the interviews, it was found that the average student had difficulty in several sub-materials, namely the concepts of specific heat, temperature, expansion, and the effect of heat on changes in temperature and phase. This research needs to be followed up to overcome students' misconceptions on heat and temperature.